(untitled) (Journal of Dhaka Medical College, 2023)
Background: The knowledge of the local pattern of infection and microorganisms in non-specific neck abscess is essential to enable efficacious treatment for it. Objective: To find out the pattern of bacteria responsible for developing non-specific neck abscess and to analyze the coverage rate of different empiric antimicrobial agents. Materials and methods: It is prospective observational type of study carried out into Department of Otolaryngology & Head Neck Surgery, Dhaka Medical College Hospital, Dhaka and Department of Clinical Microbiology, ICDDR,B, Dhaka from1st January,2016 to 30th June, 2016. Total 100(Hundred) patients were included in this study. Data were analyzed using computer based programmed statistical package for social science (SPSS). Results: This study was done among 100 patients. In this study 42 cases (42%) were in the (31- 45) years age group. The male patients were 60 (60%) and female were 40 (40%). Majority of patients 70(70%) came from poor class family with 70 (70%) patients came from rural area, 50 (50%) patients had dental infection, 40(40%) patients were smoker, 35 (35%) patients had diabetes mellitus, all the cases (100%) presented with dysphagia and fever. The major complication was necrotizing fasciitis 8 (8%), common space was sub mandibular space (45%), Streptococcus 30 (30%) was the most common organism. Conclusion: The most frequently isolated organism in neck abscess is Streptococcus. J Dhaka Med Coll. 2021; 29(1): 31-37